The drivers of Bank M&A in the Euro Area during the crisis: the role of macro determinants and non-performing loans - Roldão, Mário João Salvador (2018)
Banking sector integration in Europe reversed its momentum with the Financial Crisis, with Mergers and Acquisitions (M&A) withdrawing to national borders, in a time where uncertainty over asset quality and sovereign risk became the new paradigm. The M&A literature mostly focuses on the typical factors determining M&A in the banking industry during economic upswings yet gives little attention to periods of crisis. Taking this into account, this paper intends to shed some light on the drivers of M&A in the Euro Area during this troubled period. Making use of a multinomial logit model, results show that acquisitions during the crisis were effectively curbed by widespread credit risk, in the form of non-performing loans, and do not appear to have been spurred by supervision nor by regulation. M&A activity during this period is driven by performance and liquidity, being most intense for banks in countries under higher macroeconomic distress and exhibiting higher levels of idiosyncratic risk and poor loan quality.